Interbirth intervals in wild baboons: Environmental predictors and hormonal correlates. Issue 1 (8th February 2018) - Gesquiere, Laurence R.; Altmann, Jeanne; Archie, Elizabeth A.; Alberts, Susan C.
Abstract: Objectives: Interbirth intervals (IBIs) are a key metric of female reproductive success; understanding how they are regulated by environmental, social, and demographic factors can provide insight into sources of variance in female fitness. Materials and Methods: Using 36 years of reproductive data on 490 IBIs for 160 wild female baboons, we identified sources of variance in the duration of IBIs and of their component phases: postpartum amenorrhea (PPA), sexual cycling, and pregnancy. We also examined how body fat and fecal hormone concentrations varied during female IBIs. Results: We found that IBIs tended to be shorter (reproduction was accelerated) when female traits and environmental variables promoted energy acquisition, but with different specific effects for different component phases of the IBI. We also found that females lost a substantial amount of body fat during PPA, indicating that PPA imposes accumulating energetic costs as it progresses. Prior to cycle resumption females began to regain body fat; body fat was stable across the cycling phase and increased throughout most of pregnancy. However, body fat scores per se were not associated with the duration of any of the component phases. Finally, we found that fecal glucocorticoid concentrations decreased as PPA progressed, suggesting a decline in energetic stress over this phase. Fecal progestogen and estrogen concentrations changed over time during sexual cycling; the direction of these changes depended on the phase of the sexual cycle (luteal versus early or late follicular phases). Discussion: Our study lends insight into the energetic constraints on female primate reproduction, revealing how female environments, changes in body fat, and steroid hormone concentrations relate to IBI duration and to reproductive readiness.